Reframing widening participation towards the community: a realist evaluation. (1st July 2020) - Formby, Adam; Woodhouse, Anna; Basham, Jemma
This article draws on an evaluation of Go Higher West Yorkshire (GHWY) Uni Connect – an initiative by the Office for Students (OfS) to reduce educational inequalities through collaborative widening participation (WP) outreach across West Yorkshire. It contributes to wider debates on widening participation policy through demonstrating how Higher Education Progression Officers (HEPOs) normalised 'progression' based on community and learners' needs. We deploy realist evaluation to examine the role of HEPOs in a range of educational contexts where young people historically do not progress on to higher education (HE) at the same rates as their peers when GCSE results are taken into account. While there are complexities around the introduction of WP resources in such communities, the article highlights the importance of contextualised WP, and offers a new model of community-focused WP that incorporates learners' needs, educational institutions and the wider community space in which they reside.